Revisão sistemática do óleo essencial da espécie Plectranthus amboinicus (Lour.) Spreng. - Ferreira, Tamyris Freires (2015)
Essential oils (EOs) are volatile substances, lipophilic, usually odoriferous and liquid due to the pleasant and intense aroma of the most volatile oils found as mixtures. The EOs , depending on the plant family which are extracted, can occur in specialized secretory structures such as the glandular (Lamiaceae), o leíferos channels (Apiaceae), differentiated parenchyma cells (Laureaceae, Piperaceae, Poaceae) or lisígenas or esquizolisígenas bags (Pinaceae, Rutaceae). Moreover, they can be stored in various plant organs, such as flowers, leaves, bark, wood, roots, rh izomes, fruits and seeds. These substances have shown satisfactory results in inhibition of a variety of plant pathogenic fungi, and they have attracted scientific interest because they are characterized as natural products recognized as GRAS (Generally Re cognized as Safe) having broad spectrum antimicrobial activity and showing efficacy in controlling of pathogenic and spoilage micro - organisms of importance in vegetables. However, area of the authors have acknowledged that investigations so far are insuf ficient, making the study of SOs a field under construction and very promising. This work was central purpose of reviewing about essential oils as well as its importance to the industry, its applicability and pharmacological activities. Having specific obj ectives update the information on the essential oil of the species Plectranthus amboinicus , and their pharmacological activities. These objectives were achieved through research in search ScienceDirect databases, Biomed, Medline and Google, in addition to bibliographic collection available in the libraries of the Federal University of Paraíba during the years 2005 to 2015. It was observed that in reviewing these objectives were achieved by providing the academic community the state of the art studies on ess ential oils and can serve as a basis for future research.